Chief Financial Officer Functional Diversity and the Timeliness of Annual Reports: A Comparative Study of Firms With Different Ownership Types - Yu, Hao; Huang, Weiguang (Frontiers in Psychology, 2022)
Functional diversity is related to functional areas in which CFOs are experienced. It reflects their number of general managerial skills or social ties to some extent. This paper examines whether there is an association between CFO functional diversity and the timeliness of annual reports. Using data on Chinese listed firms from 2009 to 2017, this paper found that in state-owned enterprises, there is a negative relationship between this diversity and timeliness. However, the promotion incentive of CFOs with functionally diverse experience can weaken this negative relationship. We also found that there is a positive relationship between the two factors in private enterprises whose offices are headquartered in regions with a low degree of marketization. This paper use difference-in-differences method to test the hypotheses again. The conclusions remain robust.